2020
DOI: 10.22271/chemi.2020.v8.i2e.8784
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of spatial variability of soil fertility status in KVK farm of Pahanda in Durg district, Chhattisgarh using Gis-Gps

Abstract: The precise nutrient management is one of the most important and integral part of the modern-day agriculture. For this to happen we have to know the spatial variability of soil fertility. In this study, all soil physico-chemical properties (pH, EC, OC), Available macronutrients (N, P, K, S) and Available micronutrients (B, Fe, Mn, Cu, Zn) status with their spatial variability in KVK farm of Pahanda was quantified and based on their result soil fertility maps were prepared for respective nutrients using Arc-GIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…The soil C content was found to be low in the study area which may be due to high temperature that enhanced oxidation of native organic matter and carbon and also low rates of organic matter additions in soils. The obtained results were in line with the results obtained by research work of Meher et al [11] reported that the OC ranged from 2.7 to 7.1 g kg -1 with a mean of 4.8. g kg -1 of KVK farm Pahanda in Durg District, Chhattisgarh. Similar results were also supported by Singh et al, [12], Kumar et al, (2017), Dadsena et al [13].…”
Section: Ec (Dsm -1 )supporting
confidence: 92%
See 4 more Smart Citations
“…The soil C content was found to be low in the study area which may be due to high temperature that enhanced oxidation of native organic matter and carbon and also low rates of organic matter additions in soils. The obtained results were in line with the results obtained by research work of Meher et al [11] reported that the OC ranged from 2.7 to 7.1 g kg -1 with a mean of 4.8. g kg -1 of KVK farm Pahanda in Durg District, Chhattisgarh. Similar results were also supported by Singh et al, [12], Kumar et al, (2017), Dadsena et al [13].…”
Section: Ec (Dsm -1 )supporting
confidence: 92%
“…The very less EC value of area may be ascribed to extensive leaching of all soluble salt to deeper layer and runoff losses from surface soil layer. The results were supported by the research work done previously by Meher et al, [11], in the soils of Pahanda Durg district in Chhattisgarh state. He concluded that the EC ranged between 0.01-0.32 d Sm -1 with an average of 0.11 d Sm -1 .…”
Section: Ec (Dsm -1 )supporting
confidence: 89%
See 3 more Smart Citations